Elder Abuse in Assisted Living. (March 2013) - Castle, Nicholas; Beach, Scott
Assisted Living (AL) currently represents one of the most numerous institutional care settings for elders. Very little information exists on abuse in AL. Descriptive information on elder abuse reported by nurse aides working in AL is presented from a survey sent to nurse aides. The questionnaire had items addressing verbal, physical, psychological, caregiving, medication, material, and sexual abuse. The responses to the questions included in the verbal abuse, physical abuse, psychological abuse, caregiving abuse, medication abuse, and material exploitation abuse sections (28 questions) show that suspected abuse is not uncommon. We could not objectively verify the cases of abuse described in the survey, still, they give a first indication that staff abuse may occur in AL. This may be significant given the large number of ALs in the United States and may influence the health, quality of life, and safety of many residents.